The effects of acoustic disturbance on anaerobic endurance in female volleyball players - Sienkiewicz-Dianzenza, E.; Baranowska, M. B.; Stupnicki, R. (Human Movement, 2015)
The purpose of the study was to assess anaerobic endurance in volleyball players through repeated vertical jump performance under quiet and noisy conditions. Methods. A group of 12 female players aged 19-28 year completed six sets of eight standing vertical jump jumps; jump height and heart rate before and after the protocol were measured in quiet and noisy (fan cheering) conditions. Results. Maximum and minimum vertical jump heights were higher and intragroup differences were smaller in noisy than quiet conditions. Conclusions. Vertical jump testing, a measure of physical activity typical of volleyball, is suitable for monitoring training effects. The influence of noise typical during volleyball matches had a positive effect on player performance and anaerobic endurance.